Peningkatan Pemahaman Pencegahan Tuberkulosis melalui Sanitasi Lingkungan dan PHBS di Kelurahan Pisang, Padang - Kamal Kasra; Diva Annisa Putri; Adinda Widyastuti; Irhamni Mardhatillah Zura; Syauqi Fathan (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which primarily affects the lungs but can also involve other organs such as the kidneys, bones, brain, and lymph nodes. TB remains a significant public health concern in Indonesia, including in Pisang Village, Pauh District, which records one of the highest TB prevalence rates based on data from the Pauh Community Health Center and local government. Poor sanitation conditions and low public awareness are among the major contributing factors to the high number of TB cases in this community. This community engagement activity aimed to enhance public understanding and awareness of TB through the emotional demonstration (emo-demo) approach. This interactive method was used to effectively communicate key health messages regarding the causes, transmission mechanisms, and preventive measures of TB, while also highlighting the importance of environmental sanitation and the implementation of Clean and Healthy Living Behaviors. The results of this activity demonstrated a noticeable improvement in community knowledge and awareness related to TB symptoms, causes, transmission routes, and prevention strategies. Participants showed increased interest and understanding, indicating positive behavioral changes and greater willingness to adopt preventive practices. Therefore, the emo-demo approach proved to be an effective educational strategy for strengthening TB prevention and control efforts at the community level.